The Feminist and Orientalist Perspective in Gurindher Chadha's Bride and Prejudice - Astuti, Irma Windy (English Education Department, Universitas Islam Indonesia, 2009)
This article discusses a movie by Gurindher Chandha's Bride and Prejudice which is an adaptation of Jane Austen's Pride and Prejudice. The movie, despite being a mainstream one, contains critiques about patriarchy in Indian society and is against Western's orientalist notion about India. For these reasons, this article is trying to unfold how feminism and orientalism are presented in the movie.